Evaluation of nanomaterials to prevent oral Candidiasis in PMMA based denture wearing patients. A systematic analysis - Nafis Ahmad, Professor, MDS; Zeba Jafri, Professor, MDS; Zishan H. Khan, Professor, Ph.D (Elsevier, 2020)
Purpose: The purpose of this study is the prevention of Candida colonies on PMMA Denture Base by altering the surface and incorporations of Nanoparticles. Materials and methods: The Pub Med/Medline was searched to identify 100 relevant studies published from 2011 to 2020. The search strategy employed the following keywords related to "use of Nanoparticles in dentistry", "Antimicrobial agents and PMMA", "Candidiasis and nanomaterials", "Prevention of oral Candidiasis", "Incorporation of antimicrobial agents in acrylic dentures," "nanoparticles as therapeutic agents for denture stomatitis", "Nanodentistry" or "Nanotechnology" or "Nanocomposite" or "Nanodrugs" or "Nanomaterials". Results: Most of the studies shows that modified PMMA denture base resin containing different antimicrobial coatings and incorporation of metal oxides Nanoparticles and other nanomaterials showed antifungal activity in vitro; however some materials in higher concentration showing altered physical and mechanical properties possibly due to aggregation of Nanoparticles in the lattice of PMMA molecules. Conclusion: Metal oxides nanomaterials revealed cytotoxicity to Candida and other microbes present in oral biofilm including PMMA denture surface. Nano toxicity may attribute to direct interaction of nanoparticles with cell membrane, hindrance in protein synthesis and early adhesion & interfere with physiology of pathogens.